Method for extracting iodine from fluosilicic acid
By using an oxidizing agent in fluosilicate to oxidize iodine molecules, and using fluorinated carbon materials as adsorbents to enrich iodine to produce iodine, the problems of high energy consumption, unenvironmental protection and low adsorption capacity in the prior art are solved, and an efficient and environmentally friendly iodine recovery effect is achieved.
Patent Information
- Application Number
- CN202411713257.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
AI Technical Summary
The existing methods for extracting iodine from fluosilicate have problems such as high energy consumption, unenvironmental protection, low adsorption capacity of activated carbon and high cost.
Iodine ions are oxidized into iodine molecules by using an oxidizing agent, and then fluorinated carbon materials are enriched as adsorbent to obtain iodine. It has simple operation, high iodine recovery rate, no special equipment required, and low energy consumption.
It achieves efficient and environmentally friendly iodine recovery. The adsorbent has strong adsorption ability to iodine, corrosion resistant, can be recycled multiple times, has low cost, and is simplified in process steps, which is suitable for industrial applications.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of comprehensive utilization of fluosilicic acid, and specifically relates to a method for extracting iodine from fluosilicic acid. Background Art
[0002] Phosphate ore generally contains 0.002-0.02% iodine. During the production of wet phosphoric acid, part of it enters the wet phosphoric acid, and the other part escapes in the form of HI and is recovered with the fluorine-containing gas into the fluosilicic acid solution. A lot of fluosilicic acid is used to prepare anhydrous hydrogen fluoride. If the iodine in the fluosilicic acid is not treated, the quality of the subsequent anhydrous hydrogen fluoride product will be affected. Separating and extracting iodine not only complies with the national policy of encouraging the comprehensive utilization of associated resources, but also improves the economic benefits of enterprises.
[0003] At present, there are three commonly used processes for extracting iodine from fluosilicic acid: blowing out, adsorption and extraction. The blowing out method is to add an oxidant to fluosilicic acid to oxidize the ionic iodine in the solution into molecular iodine, then blow out the iodine with hot air, absorb it with an acidic solution containing SO2, add hydrogen peroxide to precipitate the iodine, filter and separate to obtain the finished iodine, such as patents CN108033429A and CN101323435A. Its disadvantages are high energy consumption, environmental pollution and incomplete iodine removal.
[0004] The adsorption method is: introducing oxidizing gas into fluorosilicic acid to release iodine, adsorbing it with activated carbon, and then refining it after desorption to obtain iodine, such as patents CN221296152U and CN116768161A. Its disadvantage is that the activated carbon not only adsorbs iodine but also adsorbs fluorosilicic acid, has low adsorption capacity, and has high cost for high-temperature regeneration of activated carbon.
[0005] The extraction method is: add an oxidant to fluorosilicic acid to convert the free I - Oxidized into iodine molecules I2, then add organic extractants such as carbon tetrachloride, stir thoroughly to extract iodine molecules into the organic phase, separate the organic phase from the acid phase, and then evaporate carbon tetrachloride under reduced pressure to obtain crude iodine. Supercritical carbon dioxide is also used as an extractant, such as patent CN109179329A, but it requires very high pressure and special equipment, and the cost is relatively high.
[0006] Based on this, this application was developed. Summary of the invention
[0007] The present invention aims to overcome the defects of the prior art and provide a method for extracting iodine from fluorosilicic acid. The method first uses an oxidant to oxidize iodine ions into iodine molecules, and then uses an adsorbent containing a fluorinated carbon material to enrich and obtain iodine. The method is simple to operate, has a high iodine recovery rate, does not require special equipment, and has low energy consumption.
[0008] To achieve the above object, the present invention adopts the following technical solution: A method for extracting iodine from fluosilicic acid comprises the following steps: adding an oxidant to a fluosilicic acid solution for reaction at room temperature, then adding an adsorbent for stirring and adsorption, separating the solid from the liquid, and deiodinizing the solid adsorbent to obtain iodine.
[0009] Specifically, as a case, the adsorbent can be all fluorinated carbon materials, and the fluorinated carbon materials are selected from at least one of fluorinated graphene, fluorinated carbon nanotubes, fluorinated activated carbon, etc., and the adsorbent addition amount can be 0.2-2wt% of the weight of the fluosilicic acid solution. The fluorinated carbon material can be directly used in the form of powder, and fully mixed with fluosilicic acid under stirring conditions to play the role of adsorbing iodine, but the powder is easy to float above the solution, the adsorption efficiency is poor, and it is easy to clog the filter screen during filtration.
[0010] Furthermore, the fluorinated carbon material contains fluorine, which can increase the stability of the carbon material and prevent it from being corroded by fluorosilicic acid. On the other hand, the presence of fluorine reduces the carbon material's adsorption capacity for fluorosilicic acid and increases its adsorption capacity for iodine. After multiple experimental comparisons, the fluorine content in the fluorinated carbon material is preferably 30-60wt%.
[0011] Specifically, as another case, the adsorbent may also contain fillers and binders, which are made into spherical particle adsorbents together with fluorinated carbon materials. The advantage is that the density of the spherical particles can be adjusted to be equivalent to the density of the fluosilicic acid solution, so that the adsorbent particles can be suspended in the solution and dispersed more easily and evenly, thereby improving the adsorption efficiency (if the adsorbent floats on the liquid surface or settles at the bottom, the adsorption efficiency will be reduced). Another point is that the filter screen will not be blocked during filtration and separation. The amount of adsorbent added is 0.2-5wt% of the weight of the fluosilicic acid solution.
[0012] Furthermore, the filler can be α-alumina with a mesh size of 100-300 meshes, and the binder can be polyvinylidene fluoride, etc. The filler is α-alumina, commonly known as corundum, with a density of 3.9-4.1 g / cm 3 , acid and alkali resistant, will not be corroded by fluosilicic acid, and the particle size is preferably 100-300 mesh. The binder is acid and high temperature resistant, and the preferred binder in this application is polyvinylidene fluoride (PVDF), which is not corroded in fluosilicic acid solution and can keep the adsorbent intact.
[0013] Specifically, the preparation steps of the spherical particle adsorbent can be referred to as follows: S1, dissolving the binder in N-methylpyrrolidone (NMP) to prepare a glue solution with a solid content of 0.1-5wt%; S2, adding filler to the glue solution obtained in S1, stirring evenly to obtain a mixed solution with a solid content of 2-10wt%; S3, adding the fluorinated carbon material to the mixed solution obtained in S2, stirring evenly to obtain a precursor solution with a solid content of 5-30wt%; S4, spray-drying the precursor solution obtained in S3 to obtain a spherical particle adsorbent with a diameter of 0.1-3 mm and a particle density equivalent to that of the fluorosilicic acid solution, preferably 1.0-1.5 g / cm 3 , more preferably 1.2-1.3 g / cm 3 .
[0014] Specifically, the spray drying temperature in step S4 is 150-200° C., and the flow rate is 0.5-20 L / min.
[0015] The test method for the above solid content is: weigh the test liquid m1, dry it at 150℃ for 30min and weigh the weight m2, m2 / m1=solid content.
[0016] In the method of the present invention, further, the reaction time after adding the oxidant is 10-30min, and the adsorption time after adding the adsorbent is 10-120min, and the adsorbent is used continuously for multiple times, and the iodine adsorption amount accumulates to more than 30g / kg and then deiodine. Specifically, the oxidant can be potassium permanganate, chlorine, ozone, hydrogen peroxide, etc. In order not to introduce new impurities, the present application preferably uses ozone or hydrogen peroxide, and the oxidant addition amount is 3-20 times of the theoretical demand, and the reaction after adding the oxidant is 10-30min, and the iodine ion is oxidized to iodine molecules. After adding the adsorbent, adsorption is carried out for 10-120min, and iodine molecules are enriched on the adsorbent surface. The adsorbent of the present application has a strong adsorption capacity and can be used continuously for multiple times without deiodine, until the iodine adsorption amount accumulates to more than 30g / kg and then deiodine is carried out.
[0017] The present invention does not specifically limit the deiodination method. For example, the deiodination of the solid adsorbent can be: heating the adsorbent to sublime iodine, and then condensing to obtain iodine; or it can be: soaking the adsorbent in a sulfurous acid solution to dissolve iodine into iodide ions, and then oxidizing it into iodine molecules with hydrogen peroxide, and filtering to obtain iodine.
[0018] Compared with the prior art, the method of the present invention has the following beneficial effects: The present application first uses an oxidant to oxidize iodine ions into iodine molecules, and then uses an adsorbent containing fluorinated carbon materials to enrich and obtain iodine. The operation is simple, the iodine recovery rate is high, no special equipment is required, and the energy consumption is low. Compared with conventional activated carbon, the adsorbent containing fluorinated carbon materials has a stronger iodine adsorption capacity, is corrosion-resistant, can be recycled many times, and has a low cost. Furthermore, the adsorbent is made into spherical particles with a density equivalent to that of a fluorosilicic acid solution, can be evenly suspended and dispersed in the fluorosilicic acid solution, significantly improves the iodine adsorption efficiency, does not clog the filtration, and can be returned for reuse after deiodination without regeneration treatment, which greatly simplifies the process steps and is suitable for industrial applications. DETAILED DESCRIPTION
[0019] In order to make the technical purpose, technical scheme and beneficial effects of the present invention clearer, the technical scheme of the present invention is further described below in conjunction with specific embodiments. However, the embodiments are intended to explain the present invention and cannot be understood as limiting the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in the field or the product manual shall be followed.
[0020] In the following examples, the fluorosilicic acid solution used was purchased from a domestic phosphate fertilizer factory, with a fluorosilicic acid concentration of 18 wt %, a density of 1.22 kg / L, and an iodide ion concentration of 89 mg / L. The fluorinated graphene, fluorinated carbon nanotubes, corundum (α-alumina) powder, PVDF powder, solvent NMP, activated carbon, etc. used were commercially available.
[0021] Room temperature refers to 25±5°C.
[0022] Example 1 A method for extracting iodine from fluosilicic acid: At room temperature, 100 kg of fluorosilicic acid solution was placed in a stirred container, 10 g of 30% hydrogen peroxide was added, and the reaction was continued for 10 min. Then, 1 kg of fluorinated graphene with a fluorine content of 53% was added, and stirring, infiltration, and adsorption were continued for 80 min. The fluorinated graphene was separated by filtration. Another 100 kg of fluorosilicic acid solution was taken, and the above operation was repeated, and the fluorinated graphene filtered out was still used; after repeating this for 9 times (a total of 10 adsorptions), the iodine adsorption concentration was > 70 g / kg, and the fluorinated graphene that had been adsorbed with iodine was heated to 120 ° C, and the iodine vapor was collected and condensed to obtain 71.6 g of iodine, with a recovery rate of 98.1%.
[0023] Example 2 A method for extracting iodine from fluosilicic acid: At room temperature, 100 kg of fluorosilicic acid solution was placed in a stirred container, 10 g of 30% hydrogen peroxide was added, and the reaction lasted for 30 min. Then, 2 kg of fluorinated carbon nanotubes with a fluorine content of 30% were added, and the stirring, infiltration and adsorption lasted for 60 min. The fluorinated carbon nanotubes were separated by filtration. Another 100 kg of fluorosilicic acid solution was taken, and the above operation was repeated, and the fluorinated carbon nanotubes filtered out were still used. After repeating this for 14 times (a total of 15 adsorptions), the iodine adsorption concentration was > 50 g / kg, and the fluorinated carbon nanotubes that had absorbed iodine were soaked in 10 kg of 1 wt% sulfurous acid solution for 30 min, and the fluorinated carbon nanotubes were filtered out. Then, 200 g of 30 wt% hydrogen peroxide was added to the filtrate, and the reaction was stirred for 60 min to precipitate iodine. 105.2 g of iodine was obtained by filtration and drying, and the recovery rate was 96.1%.
[0024] Example 3 A method for extracting iodine from fluosilicic acid: At room temperature, 100 kg of fluorosilicic acid solution was placed in a stirred container, 20 g of ozone was introduced by bubbling, and the reaction lasted for 20 min. Then, 0.2 kg of fluorinated graphene with a fluorine content of 58% was added, and stirring, infiltration, and adsorption were continued for 120 min. The fluorinated graphene was separated by filtration. Another 100 kg of fluorosilicic acid solution was taken, and the above operation was repeated, and the fluorinated graphene filtered out was still used; after repeating this twice (a total of 3 adsorptions), the iodine adsorption concentration was > 100 g / kg, and the fluorinated graphene that had been adsorbed with iodine was heated to 120 ° C, and the iodine vapor was collected and condensed to obtain 21.4 g of iodine, with a recovery rate of 97.8%.
[0025] Comparative Example 1 A method for extracting iodine from fluosilicic acid: At room temperature, take 100 kg of fluorosilicic acid solution in a stirring container, add 10 g of 30% hydrogen peroxide, react for 10 minutes, then add 1 kg of activated carbon, stir, soak and adsorb for 80 minutes, and filter to separate the activated carbon. Take another 100 kg of fluorosilicic acid solution, repeat the above operation, and still use the activated carbon filtered out; after repeating this 9 times (a total of 10 adsorptions), heat the activated carbon that has adsorbed iodine to 120°C, collect iodine vapor and condense to obtain 62.7 g of iodine, with a recovery rate of 85.9%.
[0026] Example 4 Preparation of spherical particle adsorbent: S1, dissolving 0.12 kg PVDF in 9.9 kg NMP to prepare a glue solution with a solid content of 1.2 wt%; S2, adding 0.2 kg of 200-mesh corundum to the glue obtained in S1, stirring evenly to obtain a mixed solution with a solid content of 3.1 wt%; S3, adding 0.8 kg of fluorinated graphene with a fluorine content of 58% to the mixed solution obtained in S2, and stirring evenly to obtain a precursor solution with a solid content of 10.2 wt%; S4, the precursor solution obtained in S3 was spray dried at 180°C with a flow rate of 1.2L / min to obtain a spherical particle adsorbent with a diameter of 0.2-1mm and a particle density of 1.22g / cm 3 .
[0027] Example 5 A method for extracting iodine from fluosilicic acid: At room temperature, 100 kg of fluorosilicic acid solution was placed in a stirred container, 10 g of 30% hydrogen peroxide was added, and the reaction lasted for 10 min. Then 1 kg of the spherical particle adsorbent obtained in Example 4 was added. After stirring, the particles were evenly dispersed in the solution. The adsorption lasted for 10 min, and the spherical particle adsorbent was separated by filtration. Another 100 kg of fluorosilicic acid solution was taken, and the above operation was repeated, and the spherical particle adsorbent filtered out was still used; after repeating this 4 times (a total of 5 adsorptions), the iodine adsorption concentration was >30 g / kg, and the spherical particle adsorbent that had adsorbed iodine was heated to 120°C, and the iodine vapor was collected and condensed to obtain 36.1 g of iodine, with a recovery rate of 99.0%.
[0028] Example 6 A method for extracting iodine from fluosilicic acid: The operation steps are basically the same as those in Example 5, except that the spherical particle adsorbent in Example 5, which has been used 5 times, is used 5 times continuously without regeneration, and 36.0 g of iodine is obtained, with a recovery rate of 98.7%. The adsorption capacity of the spherical particle adsorbent without regeneration is almost equal to that of the fresh spherical particle adsorbent.
[0029] Example 7 Preparation of spherical particle adsorbent: S1, 0.2 kg PVDF was dissolved in 10 kg NMP to prepare a glue solution with a solid content of 1.96 wt%; S2, add 0.3 kg of 250-mesh corundum to the glue obtained in S1, stir evenly to obtain a mixed solution with a solid content of 4.8 wt%; S3, adding 1.5 kg of fluorinated carbon nanotubes with a fluorine content of 52% to the mixed solution obtained in S2, and stirring evenly to obtain a precursor solution with a solid content of 16.7 wt%; S4, spray-dry the precursor solution obtained in S3 at 150°C with a flow rate of 1.0 L / min to obtain a spherical particle adsorbent with a diameter of 0.1-1.2 mm and a particle density of 1.25 g / cm 3 .
[0030] Example 8 A method for extracting iodine from fluosilicic acid: At room temperature, 100 kg of fluorosilicic acid solution was placed in a stirred container, 10 g of 30% hydrogen peroxide was added, and the reaction lasted for 15 min. Then, 1.5 kg of the spherical particle adsorbent obtained in Example 7 was added. After stirring, the particles were evenly dispersed in the solution. The adsorption lasted for 12 min, and the spherical particle adsorbent was separated by filtration. Another 100 kg of fluorosilicic acid solution was taken, and the above operation was repeated, and the spherical particle adsorbent filtered out was still used; after repeating this for 11 times (a total of 12 times of adsorption), the iodine adsorption concentration was greater than 50 g / kg, and the spherical particle adsorbent that had adsorbed iodine was heated to 120°C, and the iodine vapor was collected and condensed to obtain 58.0 g of iodine, with a recovery rate of 99.4%.
[0031] Example 9 A method for extracting iodine from fluosilicic acid: The operation steps are basically the same as those in Example 8, except that the spherical adsorbent used 12 times in Example 8 is used continuously for 12 times without regeneration, and 57.7 g of iodine is obtained, with a recovery rate of 98.9%. The adsorption capacity of the spherical particle adsorbent without regeneration is almost equal to that of the fresh spherical particle adsorbent.
[0032] In summary, the method of the present invention is simple to operate and has a high iodine recovery rate; compared with conventional activated carbon, the adsorbent containing fluorinated carbon materials has a stronger iodine adsorption capacity, is corrosion-resistant, can be recycled multiple times, and has a low cost. Furthermore, the adsorbent is made into spherical particles with a density comparable to that of the fluosilicic acid solution, and can be evenly suspended and dispersed in the fluosilicic acid solution, which significantly improves the adsorption efficiency of iodine, does not clog the filtration, and can be returned for reuse without regeneration after deiodination, greatly simplifying the process steps and being suitable for industrial applications.
Claims
1. A method for extracting iodine from fluosilicic acid, characterized in that: Under room temperature conditions, an oxidant is added to a fluosilicic acid solution for reaction, and then an adsorbent is added for adsorption, the solid and liquid are separated, and the solid adsorbent is deiodinated to obtain the product.
2. The method according to claim 1, characterized in that The adsorbent comprises a fluorinated carbon material, selected from at least one of fluorinated graphene, fluorinated carbon nanotubes, and fluorinated activated carbon, and the adsorbent is added in an amount of 0.2-2 wt % of the weight of the fluorosilicic acid solution.
3. The method according to claim 2, characterized in that The fluorine content in the fluorinated carbon material is 30-60 wt %.
4. The method according to claim 2, characterized in that: The adsorbent further contains fillers and binders, which are made into spherical particle adsorbents together with fluorinated carbon materials. The adsorbent is added in an amount of 0.2-5wt% of the weight of the fluorosilicic acid solution.
5. The method according to claim 4, characterized in that The filler is α-alumina with a mesh size of 100-300 meshes, and the binder is polyvinylidene fluoride.
6. The method according to claim 4, characterized in that The preparation steps of the spherical particle adsorbent are as follows: S1, dissolving the binder in N-methylpyrrolidone to prepare a glue solution with a solid content of 0.1-5wt%; S2, adding filler to the glue solution obtained in S1, stirring evenly to obtain a mixed solution with a solid content of 2-10wt%; S3, adding the fluorinated carbon material to the mixed solution obtained in S2, stirring evenly to obtain a precursor solution with a solid content of 5-30wt%; S4, spray-drying the precursor solution obtained in S3 to obtain a spherical particle adsorbent with a diameter of 0.1-3 mm.
7. The method according to claim 6, characterized in that The spray drying temperature in step S4 is 150-200° C., and the flow rate is 0.5-20 L / min.
8. The method according to claim 1, characterized in that The dosage of the oxidant is 3-20 times of the theoretical demand, the reaction time after adding the oxidant is 10-30 minutes, the adsorption time after adding the adsorbent is 10-120 minutes, the adsorbent is used repeatedly, and the iodine adsorption amount accumulates to more than 30g / kg before deiodination.
9. The method according to claim 1, characterized in that: The deiodination of the solid adsorbent is as follows: heating the adsorbent to sublime the iodine, and then condensing it to obtain iodine.
10. The method according to claim 1, characterized in that The deiodination of the solid adsorbent is as follows: soaking the adsorbent in a sulfurous acid solution to dissolve the iodine into iodide ions, then oxidizing it into iodine molecules with hydrogen peroxide, and filtering to obtain iodine.
Citation Information
Patent Citations
Method for extracting iodine from iodine-containing fluosilicic acid
CN101323435A
Method for deeply purifying iodine recycled from wet-process phosphoric acid and fluosilicic acid
CN108033429A
Deiodination method for producing anhydrous hydrogen fluoride by using phosphoric acid by-product fluorosilicic acid
CN109179329A
Method for recovering iodine in wet-process phosphoric acid by-product fluosilicic acid solution
CN116768161A
Device for removing iodine in fluosilicic acid
CN221296152U